Multifocal myxopapillary ependymoma associated with communicating hydrocephalus in a pediatric patient. Case report and literature review. - De Moya Jaramillo, Hugo Andres; Behaine Montes, Jose Maria; Morales Sanabria, Cesar; Quintero Rueda, Diego Alejandro (Revista Argentina de Neurocirugía, 2024)
Background. Myxopapillary ependymomas are rare intramedullary neoplasms in the pediatric population. Communicating hydrocephalus is a rare association in this kind of tumors. The treatment is the total resection without damage of the adjacent spinal roots.Objectives. To describe the association between multifocal myxopapillary ependymoma and communicating hydrocephalus in a pediatric patient ans to review the literature.Case description. We present the case of a 15-year-old patient with clinical symptoms of low back pain associated with radiculopathy in the lower limbs and subsequent development of communicating hydrocephalus with intracranial hypertension syndrome.Surgery. At first, resection of the thoracolumbar and sacral intramedullary tumor was performed. Due to post-surgical neurological deterioration, magnetic resonance was performed, which showed communicating hydrocephalus and intracranial hypertension; in a second surgical stage a ventriculoperitoneal shunt was performed. The histopathological report confirms the diagnosis of myxopapillary ependymoma. The patient progresses satisfactorily after surgery.Conclusion. Myxopapillary ependymoma associated with communicating hydrocephalus is a rare condition, its diagnosis represents a challenge due to the non-specific nature of the symptoms and images, making early and a radical intervention are the fundamental pillar of treatment to avoid long-term sequelae.
Keywords: Ependymoma; Hydrocephalus; Intramedullary Neoplasia; Ventriculoperitoneal shunt